Virtual network forwarding graph embedding based on Tabu Search - Wenzhe Wang; Peilin Hong; Defang Lee; Jianing Pei; Lei Bo (International Conference on Wireless Communications and Signal Processing, 2017)
In the next generation mobile network, the concept of virtual network slice (VNS) has been proposed to facilitate the building of a dedicated and customized logical network with isolated resources, which can be defined as a subset of network resources allocated to a virtual operator or service provider. Each VNS is associated with a virtual network function forwarding graph (VNF-FG) to accomplish the related services. However, there exists a non-negligible gap between large amount of VNS requirements and finite resources in the substrate network, hence, it is vital to implement an effective approach to embed the VNF-FGs to the substrate network. In this paper, we formulate the VNF-FG embedding (VNF-FG-E) problem as an integer linear programming (ILP) aiming to minimize the total bandwidth consumption of the substrate network. Then, the approach named VNF-FG embedding based on the Tabu-Search (E-TS) is proposed to obtain a near-optimal solution of this problem. Finally, simulation results show that E-TS can accept more VNF-FGs compared with some existing algorithms.